2021
DOI: 10.3390/ijms222212131
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicology of Metal Mixtures in Drosophila: Unique Properties of Potency and Interactions of Mercury Isoforms

Abstract: Mercury ranks third on the U.S. Agency of Toxic Substances and Disease Registry priority list of hazardous substances, behind only arsenic and lead. We have undertaken uncovering the mechanisms underlying the developmental toxicity of methylmercury (MeHg), inorganic mercury (HgCl2), lead acetate (Pb), and sodium arsenite (As). To probe these differences, we used the Drosophila model, taking advantage of three developmental transitions—pupariation, metamorphosis, and eclosion—to differentiate potentially unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Toxicant exposure is possible for the fly embryo and developing larvae. Dose-dependent larval exposure to methyl mercury, mercury chloride, lead acetate, and sodium arsenite induced larval lethality and reduced the time-delayed pupariation, metamorphosis, and eclosion, with methyl mercury as the most toxic metal compound [41]. This model also proved insightful for the study of metal mixtures.…”
Section: Dnt Studies In Drosophilamentioning
confidence: 87%
“…Toxicant exposure is possible for the fly embryo and developing larvae. Dose-dependent larval exposure to methyl mercury, mercury chloride, lead acetate, and sodium arsenite induced larval lethality and reduced the time-delayed pupariation, metamorphosis, and eclosion, with methyl mercury as the most toxic metal compound [41]. This model also proved insightful for the study of metal mixtures.…”
Section: Dnt Studies In Drosophilamentioning
confidence: 87%
“…The upregulation of serotonin and downregulation of norepinephrine in the midbrain and diencephalon leads to lower gonadotrophin synthesis and secretion (Kaminski et al 1997). The toxic effect of Arsenic in a timedependent manner on flies' development had been reported earlier by (Beamish et al 2021), but there has been no mention of the Arsenic effect on fecundity of female flies. The present study revealed that female flies' fecundity decreased by increasing the Arsenite concentration in media, which corroborated with the findings of Quansah et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…A salient example of this is seen with an examination of lead, arsenic, and two mercury isoforms, where all of these metals can delay time to pupariation. However, methylmercury selectively inhibits eclosion at lower doses (Beamish et al., 2021). Other toxic effects can alter wings, eyes, bristles, and body size.…”
Section: Measuring Toxic Exposure In the Flymentioning
confidence: 99%
“…Since there is no single assay capable of measuring all metabolites within biological systems, the metabolomic approach used to study exposed flies must be thoughtfully selected to examine metabolites that will provide the most insight as to how a toxicant alters metabolism and physiology. For instance, metabolomics analysis of flies exposed to a heavy metal such as arsenic would use targeted methods to quantify metal ions, small polar metabolites, and lipids (for examples see Beamish et al., 2021; Carvalho et al, 2012; Li & Tennessen, 2018). Individual studies must also choose whether to employ a targeted approach designed to quantify a predetermined set of metabolites, an untargeted approach, which aims to measure as many metabolites as possible, or a hybrid method.…”
Section: The Emerging Importance Of Metabolomics‐based Toxicologic St...mentioning
confidence: 99%